Pengaruh Social Media Marketing dan Electronic Word of Mouth terhadap Keputusan Pembelian pada Mie Gacoan di Kota Malang - Gigih Putranda; Sanita Dhakirah; Arni Utamaningsih (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
In the digital era, social media has become an essential marketing tool for the Indonesian culinary industry, including Mie Gacoan, which utilizes Instagram to boost brand awareness and sales. Social media marketing and electronic word of mouth (e-WOM) strategies play a significant role in influencing consumer purchasing decisions by building trust and audience engagement. This study aims to analyze the influence of these two factors on consumer purchasing decisions at Mie Gacoan's Sukun branch in Malang City, an area with substantial market potential that remains underexplored. Using a quantitative approach with the variables Social Media Marketing, Electronic Word of Mouth, and Purchasing Decision, data were collected through an online questionnaire distributed to 100 respondents who are Mie Gacoan consumers, using nonprobability sampling with a purposive sampling technique, and analyzed through multiple linear regression and hypothesis testing. Descriptive analysis showed that respondents generally agreed with the questionnaire statements, and the classical assumption tests confirmed that the data met the required criteria. The coefficient of determination was 0.42 (42%), with the remaining 58% explained by other variables. The findings indicate that Social Media Marketing and Electronic Word of Mouth have both partial and simultaneous effects on Purchasing Decisions at Mie Gacoan's Sukun branch in Malang City. Therefore, Mie Gacoan's Sukun branch is advised to consider these two strategies as key components in attracting and retaining customers.